2021
DOI: 10.3390/antibiotics10101257
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High-Dose Anti-Infective Agents on the Osteogenic Response of Mesenchymal Stem Cells

Abstract: Treatment of infected nonunions and severe bone infections is a huge challenge in modern orthopedics. Their treatment routinely includes the use of anti-infective agents. Although frequently used, little is known about their impact on the osteogenesis of mesenchymal stem cells. In a high- and low-dose set-up, this study evaluates the effects of the antibiotics Gentamicin and Vancomycin as well as the antifungal agent Voriconazole on the ability of mesenchymal stem cells to differentiate into osteoblast-like ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 46 publications
6
8
0
Order By: Relevance
“…For Gentamicin and Vancomycin, it seems that the reduction in cell number does not lead to a reduction in osteogenic potential. These results are consistent with earlier findings [27]. In a study from 2021, we showed that osteogenically differentiated BM-hMSCs cultures always showed an uptake of around 3.5 MBq, whether antibiotics were added to the cell culture medium or not.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…For Gentamicin and Vancomycin, it seems that the reduction in cell number does not lead to a reduction in osteogenic potential. These results are consistent with earlier findings [27]. In a study from 2021, we showed that osteogenically differentiated BM-hMSCs cultures always showed an uptake of around 3.5 MBq, whether antibiotics were added to the cell culture medium or not.…”
Section: Discussionsupporting
confidence: 93%
“…In our data, the calcium concentration was significantly lower for all osteogenic conditions when compared to the control conditions. Vice versa, high phosphate concentrations probably correlate with osteogenesis [27]. In our data, the phosphate concentration was always significantly higher for the osteogenic groups.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Since its discovery in the 1950s, vancomycin has become widely used because of its excellent activity against both Clostridium difficile in pseudomembranous enterocolitis and methicillin-resistant Staphylococcus aureus (MRSA) [ 21 ]. Regardless of its beneficial effects, vancomycin is also known for having cytotoxic effects on mesenchymal stromal cells and osteoblasts, as well as chondrocytes [ 22 , 23 , 24 , 25 ]. A meta-analysis on the effect of intrawound vancomycin powder application (1–2 g) in knee and hip arthroplasty revealed an effective infection prophylaxis but an increase in aseptic wound complications [ 26 ], raising concerns about the healing process.…”
Section: Introductionmentioning
confidence: 99%